1999
DOI: 10.1007/s004399900089
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in the apolipoprotein H (β2-glycoprotein I) gene affects plasma apolipoprotein H concentrations

Abstract: Apolipoprotein H (apoH, protein; APOH, gene) is a single chain glycoprotein that exists in plasma both in a free form and in combination with lipoprotein particles. ApoH has been implicated in several physiologic pathways, including lipid metabolism, coagulation, and the production of antiphospholipid antibodies. The wide range of interindividual variation in plasma apoH levels is thought to be under genetic control, but its molecular basis is unknown. APOH displays a common structural polymorphism with the oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 62 publications
(61 reference statements)
0
26
0
3
Order By: Relevance
“…1B; Table 3). Previous studies have found associations of Cys306Gly and Trp316Ser with plasma apoH levels (25,26). Because the strongest associations were found for SNP 14917 (Cys306Gly), we investigated the effects of this APOH variant on DCT measures in MAs.…”
Section: Discussionmentioning
confidence: 98%
“…1B; Table 3). Previous studies have found associations of Cys306Gly and Trp316Ser with plasma apoH levels (25,26). Because the strongest associations were found for SNP 14917 (Cys306Gly), we investigated the effects of this APOH variant on DCT measures in MAs.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, the two SNPs from the CEP112 genomic region lie very close to APOH , which also appeared among the suggestive hits with intergenic polymorphism rs10048158 (at ~ 11 kbp upstream of APOH ). Subsequent LD analysis with data from the CEU population showed that the minor allele of rs10048158 is preferentially associated with the minor alleles of rs1801692 and rs1801690 ( D ′ = 1), the two missense mutations that have been reported to influence plasma β 2 ‐GPI levels . This observation suggests that rs10048158 actually represents the same association signal as rs1801692 and rs1801690 previously did.…”
Section: Resultsmentioning
confidence: 71%
“…We used a dualspecific ELISA in which antibodies to apoD bound intact apoB-containing lipoproteins equally efficient as antibodies specific for apoB. This property was unique for apoD and was not seen with other exchangeable apolipoproteins such apoE, apoH and apoJ, all of which are present in HDL and LDL/VLDL lipoprotein particles [32,33,34]. Adding detergent inhibited the apoD-mediated binding of apoB, demonstrating that changes in the LDL structure affect the formation of the complex.…”
Section: Discussionmentioning
confidence: 99%